PHYSICAL AND SPECIAL PHYSICAL PREPAREDNESS OF BOXING STUDENTS IN THE PROCESS OF PHYSICAL EDUCATION - Nazymok, V. V. (Rehabilitation and Recreation, 2021)
The aim of the study was to trace the dynamics of development of general and special physical fitness of students engaged in boxing in the process of physical education for one and two years, respectively. Muscle strength – first-year students improved their score from 28.77 to 29.75 times in a year, second- year students from 30.09 to 31.16 times in 20 seconds, and the first from 50.22 to 52.11 times, the second from 54.66 to 56.55 times in 1 minute. Special physical fitness – first course from 53.53 to 56.51 times second from 57.29 to 60.38 times left hand and first course from 57.03 to 59.62 times second from 60.29 to 63.03 times right. Explosive strength testing – during the first course from 212.85 cm to 217.12 cm during the second from 219.81 cm to 225.2 cm. The results of the first course p> 0.05, the second p <0.05. Average speed indicators showed a slightly different dynamics of development, so in the first year the results improved from 13.8 s. up to 13.71 s. and on the second worsened from 13.67 s. up to 13.76 s. The first course p> 0.05, the second p <0.05. Endurance: the average of first-year students improved from 13.34 minutes up to 13.23 minutes the second of 13.26 minutes up to 13.09 minutes Significance was the first course p> 0.05, the second p <0.05. Dexterity test – the first course from 95.07 to 100.83, the second from 112.48 to 118.64. Comparing the average testing rates of first and second year students engaged in boxing in the process of physical education, we can conclude that the general and special physical fitness of first year students according to the results of testing all physical qualities have improved. While the results of second-year students were better in all tests except speed.